Encapsulation of morin in lipid core/PLGA shell nanoparticles significantly enhances its anti-inflammatory activity and oral bioavailability - Suhair Sunoqrot; Malak Alkurdi; Abdel Qader Al Bawab; Alaa M. Hammad; Rabab Tayyem; Ali Abu Obeed; Mohammed Abufara (Elsevier, 2023)
Morin (3,5,7,2',4'-pentahydroxyflavone; MR) is a bioactive plant polyphenol whose therapeutic efficacy is hindered by its poor biopharmaceutical properties. The purpose of this study was to develop a nanoparticle (NP) formulation to enhance the bioactivity and oral bioavailability of MR. The nanoprecipitation technique was employed to encapsulate MR in lipid-cored poly(lactide-co-glycolide) (PLGA) NPs. The optimal NPs were about 200 nm in size with an almost neutral surface charge and a loading efficiency of 82%. The NPs exhibited sustained release of MR within 24 h. In vitro antioxidant assays showed that MR encapsulation did not affect its antioxidant activity. On the other hand, anti-inflammatory assays in lipopolysaccharide-stimulated macrophages revealed a superior anti-inflammatory activity of MR NPs compared to free MR. Furthermore, oral administration of MR NPs to mice at a single dose of 20 mg/kg MR achieved a 5.6-fold enhancement in bioavailability and a prolongation of plasma half-life from 0.13 to 0.98 h. The results of this study present a promising NP formulation for MR which can enhance its oral bioavailability and bioactivity for the treatment of different diseases such as inflammation.